Comparison of Morphological, Virulence, and Antifungal Susceptibility Characteristics Within Aspergillus Lentulus - Wang X; Gao C; Yusufu A; Nuermaimait X; Abliz P (Infection and Drug Resistance, 2025)
Xiaodong Wang,1 Cuirong Gao,2 Aikedai Yusufu,1 Xiyidan Nuermaimait,1 Paride Abliz1 1Department of Dermatology, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of China; 2Rheumatism and Immunology Department, First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People’s Republic of ChinaCorrespondence: Paride Abliz, Department of Dermatology, the First Hospital of Xinjiang Medical University, No. 393, Xinyi Road, Urumqi, Xinjiang, People’s Republic of China, Email palidae@aliyun.comBackground: The emerging pathogenic species Aspergillus lentulus, within the Aspergillus fumigatus complex, poses a significant threat to patient health owing to its high rates of drug resistance and mortality. The aim of this study was to characterize the intraspecies morphology, virulence, and in vitro antifungal susceptibility of A. lentulus.Methods: We cultured A. lentulus isolates from different sources (three clinical isolates and one environmental isolate), along with A. fumigatus (n=1) and Aspergillus fumigatiaffinis (n=1), to observe colony color, diameter, sporulation timing, and spore production. Virulence was assessed using a Galleria mellonella infection model, and survival curves were generated to evaluate strain pathogenicity. Antifungal susceptibility was determined using the colorimetric microdilution method with Sensititre YeastOne® panels.Results: Compared to A. fumigatus and A. fumigatiaffinis, A. lentulus exhibited whitish colonies with pale green overtones, delayed sporulation initiation, and reduced spore yield. The four A. lentulus isolates showed intrastrain variability in the timing of colony color transition, growth rates, sporulation onset, and spore quantification. Virulence experiments demonstrated that all A. lentulus isolates successfully infected G. mellonella larvae and exhibited concentration- and time-dependent survival patterns. Clinical isolates consistently showed significantly lower larval survival rates than the environmental isolates at all infection concentrations. Antifungal susceptibility testing revealed the following minimum inhibitory concentration (MIC) ranges for A. lentulus: posaconazole 0.5– 2 μg/mL, itraconazole 1– 2 μg/mL, and voriconazole 2– 8 μg/mL. Specifically, the clinical isolate A. lentulus- 10199 and environmental isolate A. lentulus- 10201 exhibited elevated voriconazole MICs (8 μg/mL). All strains demonstrated high MICs for amphotericin B (≥ 4 μg/mL) and caspofungin (≥ 8 μg/mL).Conclusion: Aspergillus lentulus exhibited both interstrain and intrastrain variations in growth rate and sporulation characteristics. Clinical isolates demonstrated greater virulence potential than environmental isolates. Aspergillus lentulus displayed favorable susceptibility to posaconazole but reduced susceptibility to voriconazole, amphotericin B, and caspofungin.Keywords: Aspergillus lentulus, virulence, antifungal susceptibility testing, azole, Aspergillus fumigatus complex